2021
DOI: 10.1037/abn0000678
|View full text |Cite
|
Sign up to set email alerts
|

Does crude measurement contribute to observed unidimensionality of psychological constructs? A demonstration with DSM–5 alcohol use disorder.

Abstract: Mental disorders are complex, multifaceted phenomena that are associated with profound heterogeneity and comorbidity. Despite the heterogeneity of mental disorders, most are generally considered unitary dimensions. We argue that certain measurement practices, especially using too few indicators per construct, preclude the detection of meaningful multidimensionality. We demonstrate the implications of crude measurement for detecting construct multidimensionality with alcohol use disorder (AUD). To do so, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 62 publications
(91 reference statements)
4
52
0
Order By: Relevance
“…Interestingly, studies have shown that these symptom clusters have differing predictive validity, specifically that tolerance/excessive consumption symptoms are a poor predictor of overall AUD severity and other forms of psychopathology [4,10,11]. Wakefield and Schmitz [10,11] posited that individuals who only have problems with excessive consumption (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, studies have shown that these symptom clusters have differing predictive validity, specifically that tolerance/excessive consumption symptoms are a poor predictor of overall AUD severity and other forms of psychopathology [4,10,11]. Wakefield and Schmitz [10,11] posited that individuals who only have problems with excessive consumption (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, behavior genetic studies have indicated that there are disparate, although correlated, genetic risks for alcohol tolerance/excessive consumption versus other types of alcohol problems [7, 9]. Interestingly, studies have shown that these symptom clusters have differing predictive validity, specifically that tolerance/excessive consumption symptoms are a poor predictor of overall AUD severity and other forms of psychopathology [4, 10, 11]. Wakefield and Schmitz [10, 11] posited that individuals who only have problems with excessive consumption (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Identity Disturbance, (2) Self-harm, and (3) Detachment. As we demonstrated here, with more thorough tests of alternative models, we are less likely to confuse good CFA model fit with good theoretical support (see also Watts et al, 2020Watts et al, , 2021. Do: Remember that measurement affects your output.…”
Section: Do: Report Factor Reliabilitymentioning
confidence: 75%
“…With ESEM, we can examine whether the proposed 3-factor CFA of borderline, paranoid, and schizoid PD symptoms is tenable, in the sense that it is well supported in more exploratory analyses (see also Greene et al, 2022;Watts, Boness, et al, 2021) and whether model fit improves after relaxing the assumption of simple structure (Ex. 2).…”
Section: Exploratory Structural Equation Modeling Exploratory Structu...mentioning
confidence: 99%
“…Next, we conducted a series of EFAs to probe evidence of anomalous results in previous work and to test whether the models derived by CFA would also emerge with limited input from the researcher (Watts et al, 2021). Confirmatory approaches are clearly valuable given a strong theory about the latent structure of a set of observed variables, but contemporary CFA model comparisons typically proceed in a covertly exploratory manner (Asparouhov & Muthén, 2009; Brown, 2015; Browne, 2001; MacCallum et al, 1992; Schmitt et al, 2018).…”
Section: Extending Tom Swift’s Electric Factor Analysis Machine To Qu...mentioning
confidence: 99%